The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1808-86942010000100018
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da idade materna, paterna, ordem de paridade e intervalo interpartal para fissura lábio-palatina

Abstract: Cl eft lip and palate (CL/P) are the most common congenital craniofacial anomalies. Aim: To evaluate environmental risk factors for non-syndromic CL/P in a reference care center in Minas Gerais. Materials and Methods: we carried out a case-controlled study, assessing 100 children with clefts and 100 children without clinical alterations. The analysis dimensions (age, skin color, gender, fissure classification, maternal and paternal age, birth order and interpregnancy interval), obtained from a questionnaire; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 30 publications
2
3
0
2
Order By: Relevance
“…In this present study, the sample characterization with predominance of males in G1, corroborated other studies 18,19 . Epidemiological findings have shown gender differences in incidence, prevalence, during alterations of development and behavior 20 , however, in the population with cleft lip and palate, prospective studies have not been registered to justify this rate, due to the wide range of genetic and teratogenic factors related, although there is a higher prevalence for females, as for post-foramen type, and a prevalence for males, as for pre and trans-foramen types 14 .…”
Section: Discussionsupporting
confidence: 93%
“…In this present study, the sample characterization with predominance of males in G1, corroborated other studies 18,19 . Epidemiological findings have shown gender differences in incidence, prevalence, during alterations of development and behavior 20 , however, in the population with cleft lip and palate, prospective studies have not been registered to justify this rate, due to the wide range of genetic and teratogenic factors related, although there is a higher prevalence for females, as for post-foramen type, and a prevalence for males, as for pre and trans-foramen types 14 .…”
Section: Discussionsupporting
confidence: 93%
“…Second, due to the small sample size and the low exposure rates of some of the investigated factors, some common important risk factors were not included in the prediction model, such as maternal age, folic acid intake, history of infection during pregnancy, mothers’ abnormal reproductive history, medication use during pregnancy, maternal stressful events during pregnancy, tobacco, and alcohol. Many of the published papers show conflicting results on the relationship between maternal age and NSCL/P [10, 12, 41]. The effect of folic acid on NSCL/P has generated debate in previous studies [28, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, most studies have focused on the identification of risk factors of NSCL/P. Many epidemiological studies have confirmed that maternal age [1012], maternal educational level [2, 13], family income [13, 14], abnormal reproductive histories [15], family history [1416], history of infection during pregnancy [17], medication use during pregnancy [18, 19], ambient environment pollution [20], parental occupational hazards exposure [2123], maternal nutrient intake [2326], and maternal lifestyle factors (alcohol drinking, smoking) [2729] are associated with NSCL/P. However, an individual risk prediction tool for NSCL/P has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The higher occurrence in males was also found in Brazil 22,23 and in other parts of the world 24,25 . Related to the type of cleft, the findings in this study confirm the predominance of the transforamen cleft, as observed by other researchers 2,15,21,22 . In the Coope et al study (2000) 21 for instance, the occurrence of cleft lip and palate (65%) was approximately twice as high as cleft lip only (35%).…”
Section: Discussionmentioning
confidence: 52%